2022
DOI: 10.1097/as9.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Technical Modifications to the Associating Liver Partition and Portal Vein Ligation for Staged Hepatectomy (ALPPS) Procedure

Abstract: Objectives: To compare the outcomes of modified-Associating Liver Partition and Portal vein Ligation for Staged hepatectomy (ALPPS) techniques with those of conventional-ALPPS. Background: ALPPS is an established technique for treating advanced liver tumors. Methods: PubMed, Web of Science, and Cochrane databases were searched. The outcomes were assessed by single-arm and 2-arm analyses. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…However, externalization of biliary flow facilitates the remission of liver function and avoids the endotoxemia [53]. Recent studies have demonstrated that functional and volumetric hypertrophy were similar after the first stage of both conventional and modified ALPPS; therefore, modified ALPPS is preferred because it lowers morbidity and mortality without compromising other treatment outcomes [10,54]. Although a direct comparison between different modifications of ALPPS, such as partial ALPPS, radiofrequency-assisted ALPPS, and associating liver tourniquet and portal vein ligation for staged hepatectomy (ALTPS) was not possible due to not enough available data, a recent meta-analysis revealed similar outcomes from different techniques, using a single-arm meta-analysis [54].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, externalization of biliary flow facilitates the remission of liver function and avoids the endotoxemia [53]. Recent studies have demonstrated that functional and volumetric hypertrophy were similar after the first stage of both conventional and modified ALPPS; therefore, modified ALPPS is preferred because it lowers morbidity and mortality without compromising other treatment outcomes [10,54]. Although a direct comparison between different modifications of ALPPS, such as partial ALPPS, radiofrequency-assisted ALPPS, and associating liver tourniquet and portal vein ligation for staged hepatectomy (ALTPS) was not possible due to not enough available data, a recent meta-analysis revealed similar outcomes from different techniques, using a single-arm meta-analysis [54].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that functional and volumetric hypertrophy were similar after the first stage of both conventional and modified ALPPS; therefore, modified ALPPS is preferred because it lowers morbidity and mortality without compromising other treatment outcomes [10,54]. Although a direct comparison between different modifications of ALPPS, such as partial ALPPS, radiofrequency-assisted ALPPS, and associating liver tourniquet and portal vein ligation for staged hepatectomy (ALTPS) was not possible due to not enough available data, a recent meta-analysis revealed similar outcomes from different techniques, using a single-arm meta-analysis [54]. Furthermore, considering the complexity of the ALPPS procedure and the importance of the precise patients' selection, the ALPPS risk score was developed to identify patients at risk of early ALPPS-related morbidity and mortality [19,26,55].…”
Section: Discussionmentioning
confidence: 99%